SOSIALISASI PENTINGNYA MENJAGA DAN MELESTARIKAN LINGKUNGAN PADA SMA NEGERI 1 MONTONG GADING LOMBOK TENGAH: Socialization Of the Importance of Protecting and Preserving the Environment at State Senior High School 1 Montong Gading, Central Lombok - Muhamad Yamin; Bagus Widhi Dharma S. Dharma S.; Agus Winardi; Wiriyanti Isnasari; Isnaeni Isnaeni; Rahman Rahman; Yuan Sa’adati; Aminullah Aminullah (Al-Amal: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to increase public understanding and awareness, especially among the younger generation, regarding the importance of protecting and preserving the environment. The main problems currently faced by the community are low awareness of waste management, environmental pollution, and lack of participation in maintaining the cleanliness of the surrounding environment. The activity implementation method is carried out through socialization, counseling, interactive discussions, and simple practices regarding good environmental management. The activity was carried out by involving students of SMA Negeri 1 Montong Gading, East Lombok Regency as the main participants. The results of the activity showed that the students showed high enthusiasm for the material provided. After the socialization, participants began to understand the negative impacts of environmental pollution and the importance of implementing clean and healthy lifestyle behaviors. In addition, the community also began to understand the importance of reducing plastic use, managing household waste, and greening the environment. This activity has a positive impact in the form of increased awareness among the younger generation to maintain environmental cleanliness and sustainability in a sustainable manner.